PENDAMPINGAN KESIAPAN KEPEMIMPINAN GLOBAL MELALUI PEMBELAJARAN BAHASA ASING BERBASIS ISU-ISU INTERNASIONAL - Djunaidi, Djunaidi; Suleman, Zulfikri; Khairunnas, Khairunnas; Rafinzar, Rahmad (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2024)
One paragraph, containing the objectives, research methods used, and results. Globalization has a comprehensive impact on all sectors throughout the world. Globalization has a very significant impact and brings various currents of international issues that become challenges for various countries. In reality, globalization encourages various diplomatic steps between countries, both aimed at increasing development, as well as cooperation that helps in alleviating various domestic public problems and state challenges in the future. All the problems and issues that currently no longer recognize national borders have caused international communication tools or languages to become one of the basic needs of the world community, especially in forming the character and leadership skills of the younger generation who are ready to be involved globally in the future, so that the aim of the activity This is to provide an understanding of how to build global leadership character and the importance of mastering a foreign language as a tool of international communication and an instrument in understanding global issues, and can be done using fun methods, the method used is a mentoring activity which consists of 2 activity session, namely the delivery of several materials and foreign language learning using the game method. The results of this activity are to provide the effect of understanding and skills for participants about global leadership and the importance of mastering foreign languages as a tool of international communication and can be done using fun methods